REPRESENTATION OF FEMINISM FROM THE MAIN CHARACTER IN MULAN MOVIE - Fazrina, Fazrina; Abdullah, Abdullah; Mahmud, Murni (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2024)
The design of research used is qualitative research. According to Bogdan and Taylor (2022), qualitative research is a research procedure that is capable of producing descriptive data in the form of speech, writing and behavior of people being observed. This qualitative research aims to understand the status of the context to guide the interpretation of detailed and in-depth descriptions of natural conditions, based on existing reality. According to Strauss and Corbin (in Faridah Nugrahani 2014) qualitative research is a type of research whose findings are not obtained through statistical procedures or other forms of computing. Qualitative research produces descriptive data that describes the subject's situation in words and pictures, not numbers. The 2020 film challenges societal stereotypes that portray women as weak, unreliable, or incapable of learning self-defense. Instead, it presents women as strong, intelligent, and determined, demonstrating courage and resilience. The research also indicates that the film maintains a balance between showcasing feminist themes and preserving traditional feminine qualities. This is evident in Mulan's style, clothing, and her emotional response when she is expelled from the regiment.Keywords— Representation, and Feminism from the Main Character in Mulan Movie.